Problem Formulation as the Reduction of a Decision Model - Heckerman, David; Horvitz, Eric (2009)
In this paper, we extend the QMR-DT probabilistic model for the domain of internal medicine to include decisions about treatments. In addition, we describe how we can use the comprehensive decision model to construct a simpler decision model for a specific patient. In so doing, we transform the task of problem formulation to that of narrowing of a larger problem.
SRC Technical Note 1998-004 (March 1998). Rejected by Information Processing Letters.